2016
DOI: 10.1021/acs.jpcc.6b00496
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Intercalation Induced by Photocatalysis on the Surface of Hybrid Lead Halide Perovskites

Abstract: Methylammonium lead iodide (MAPbI 3 ) perovskite has emerged as a dazzling nova in the solar cell realm. However, the robustness or stability of the material exposed to different ambiences is a key issue. In this paper, resonance Raman spectroscopy is combined with surface and bulk crystal characterizations to interpret the oxygen intercalation phenomenon on the surface of MAPbI 3 . We observe that oxygen can intercalate into the frameworks of MAPbI 3 with the assistance of laser excitation. By lowering down t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 31 publications
1
59
0
Order By: Relevance
“…Similar formation of PbO x lead oxide is observed also for the films on glass (Figure 4 Recently Kong et al 48 reported that oxygen intercalation into the frameworks of , therefore a certain concentration of vacancies will be present. The evolution of Raman spectra is similar for the films in all substrates except that for PEDOT:PSS where PbO x phase cannot be identified, see Figure S7.…”
Section: Films On Different Substratessupporting
confidence: 68%
“…Similar formation of PbO x lead oxide is observed also for the films on glass (Figure 4 Recently Kong et al 48 reported that oxygen intercalation into the frameworks of , therefore a certain concentration of vacancies will be present. The evolution of Raman spectra is similar for the films in all substrates except that for PEDOT:PSS where PbO x phase cannot be identified, see Figure S7.…”
Section: Films On Different Substratessupporting
confidence: 68%
“…These observations indicate that the presence of oxygen and water vapor in air plays an important role, likely related to the photochemical reactions at the perovskite crystal surface. 40,4649 A detailed discussion on this point can be found in a later section, where PL blinking under different environmental conditions is reported (Figure 6). …”
Section: Results and Discussionmentioning
confidence: 84%
“…Despite the high device efficiency, solution process at a low cost, and potential for large‐scale manufacturing, the stability of the perovskite solar cells is one major challenge that impedes commercialization . Several factors that affect the stability of hybrid perovskites have been systematically investigated, such as humidity, oxygen, heat, and irradiation . When exposed to humidity, the perovskite hydrate CH 3 NH 3 PbI 3 · x H 2 O forms, driving the perovskite crystal decomposition to PbI 2 .…”
Section: Introductionmentioning
confidence: 99%